2011
DOI: 10.2190/cs.13.2.d
|View full text |Cite
|
Sign up to set email alerts
|

The Bounce Back Retention Program: One-Year Follow-UP Study

Abstract: This study provides results regarding the effectiveness of the Bounce Back Retention Program (BBRP), a semester-long voluntary course for students on academic probation (AP). This is the first phase of a longitudinal study of spring 2007 freshmen at San Diego State University (SDSU). Results were analyzed for three samples: 1) AP BBRP-Credit enrolled and earned course credit (n = 81); 2) AP-BBRP No Credit enrolled but failed to earn course credit (n = 44); and 3) AP-NonBBRP did not enroll in BBRP but were on A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…Because all students in a course influence the classroom dynamic and this study was interested in process variables, it is unknown how students in the class who opted not to participate may have impacted their course sections. This appears to be a concern unique to this study, as other studies of academic enhancement interventions have reported the participation of all enrolled students (Coleman & Freedman, 1996;Hanger et al, 2011;Kamphoff et al, 2007;McGrath & Burd, 2012;Mellor et al, 2015). Future studies might advocate for assessment being a required component of the course.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Because all students in a course influence the classroom dynamic and this study was interested in process variables, it is unknown how students in the class who opted not to participate may have impacted their course sections. This appears to be a concern unique to this study, as other studies of academic enhancement interventions have reported the participation of all enrolled students (Coleman & Freedman, 1996;Hanger et al, 2011;Kamphoff et al, 2007;McGrath & Burd, 2012;Mellor et al, 2015). Future studies might advocate for assessment being a required component of the course.…”
Section: Discussionmentioning
confidence: 93%
“…Robbins et al (2004) note that these skills are necessary to complete academic tasks, and therefore are likely connected to performance outcomes. Much of the existing research on classroom-based interventions has described course content with a significant focus on academic-related skills, though the entire intervention served as the independent variable so the association between individual skills and academic performance is unknown (Hanger et al, 2011;Humphrey, 2006;Kamphoff et al, 2007;McGrath & Burd, 2012;Mellor et al, 2015). Future studies might measure growth of specific skills throughout the intervention and their association with academic performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many academic and personal challenges can contribute to failure. Students entering college are often suddenly faced with considerable challenges and demands in all spheres of their lives 3 . Changes in personal responsibilities associated with growing up and increases in academic expectations can make the transition into college particularly difficult.…”
Section: Literature Reviewmentioning
confidence: 99%